PROGRAM PELATIHAN KERJA OLEH DINAS TENAGA KERJA KOTA PEKANBARU TAHUN 2015 - Nona Widyana; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Demans the world of work to labor skilled encourage job seekers to follow job training to increase their skills. Department of labor the city of Pekanbaru make and conducted programs employment to job seekers by making program namely the program job training engaged with their job training private that is there Pekanbaru. The number of employment after conducted training in 2015 more than 50% of where as many as 102 participants to get a job. It means the implementation of the program as expected where participants who trained get a job and make their own business. The purpose of this research is want to see the training programs worked by department of labor city of Pekanbaru 2015 and know factors anything influence it.Researchers used Moekijat Theory which states that components in training namely the participants, instructrur training, time training, the training material and methods of training. This research use the method descriptive qualitative, technique data collection though observation and interview where parties involved in this research as informants.The result of this research indicates that process of job training program by the work in Pekanbaru 2015 going well where labor absorbed more than 50%. This may be because the five components of the training done well. The factors affect the job training programs by the department of labor city Pekanbaru 2015 is good coordination between all enforcement authorities job training programs and than facilities and infrastructure.Keywords : Job Training Program, Participants Training and Departement Of The City Of Pekanbaru.